RETRACTED ARTICLE: Modification gelatin scaffold with carboxymethylcellulose for dermal skin - Wiwatwongwana,F. (2015)
Effects of carboxymethylcellulose (CMC), a derivative of cellulose, blended with biopolymer gelatin scaffolds were studied. The CMC solution was mixed with gelatin solution in various ratios and fabricated to porous structure via freeze drying process. Thermal and chemical crosslinking techniques were used to induce conjugation of free amide and carboxyl groups in protein structures of the different types of scaffold. Physical and mechanical properties of different gelatin/CMC scaffolds were characterized via Scanning Electron Microscope (SEM) which observe of a scaffold cross section. The compressive modulus of the scaffolds were evaluated via Universal Testing Machine (UTM). The morphology of the gelatin/CMC scaffolds seemed to mainly depend upon the mixing ratios of gelatin and CMC solutions. Adding of CMC to the scaffolds decreased in pore sizes and seemed to have more porous than pure gelatin scaffolds, especially when used the 1-ethyl-3-3- dimethylaminopropyl carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) in 50 mM MES buffer in 40% ethanol for crosslinking the scaffolds. The mechanical analysis demonstrated that adding CMC effected the compressive modulus of the EDC/NHS crosslinked scaffolds. The compressive modulus dramatically decreased when increased of CMC in some ratio in the scaffolds. These results suggested that using CMC as an additive and crosslinking techniques improved physical properties of the scaffolds. However, the compressive modulus of the scaffolds decreased in some ratio both thermal and chemical crosslinking techniques. This results suggested that the additive of CMC had tendency to display some interesting properties for applying in tissue engineering applications. © 2011 IEEE.